Alley coppice: an innovative land use system - options of system design with experimental evidence - Paris, P. (2014)
Agroforestry and Short Rotation Coppice (SRC), for timber and bioenergy wood production, are recognized as economically viable and sustainable as separate cropping systems under ideal growing conditions. Little is known about agricultural and ecological interactions which might occur combining them in a tree-based intercropping system. This mixed approach, called alley coppice, is currently investigated in an European research Project (www.agrocop.com), and has important advantages: (i) a regular income guaranteed from the SRC component; (ii) light competition between species can often improve the stem form of timber trees; (iii) timber trees can be planted at the final spacing, avoiding expensive thinning; (iv) SRC component protects young timber trees from wind/storm damage; (v) alley coppice is expected to have positive impacts on biodiversity, and reducing soil erosion. Three system designs are currently investigated: Simultaneous planting (SP); Lagged planting (LP) and Border planting (BP). In SP, timber and SRC components are planted in the same year; the key investigated factor is the distance between timber trees and the first SRC row, comparing 1, 2, 3 m in plantations in Ireland, Germany and Italy. A tree row width of three meters guaranteed satisfying growth rates of Sorbus and Pyrus timber trees in a mixture with 2-yr SRC poplar (Populus spp) in Italy, improving timber wood quality. LP, with planting SRC under adult timber trees, is studied in France and Ireland, according to timber tree age, species and inter-row spacings. In France, light and water competition had significant effects on poplar SRC growth and yield according to the distance from the walnut trees. BP involves planting timber trees along the borders of SRC blocks. Experimental plantations were established in Ireland and Germany, with the aim of avoiding asymmetric light competition that might hamper stem form of timber trees. Guidelines for practitioners on alley coppice optimization will be provided at the end of the project.